Method for minimization of the phase volume growth on the post-stripping section of the UNILAC - Barth, W.; Bomko, V.O.; Dahl, L.; Groening, L.; Kobets, A.P.; Tishkin, S.S.; Yaramyshev, S.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2007)
The method for determination of the optimum parameters of the matching line of UNILAC post-stripping section (Alvarez structure) is presented. The distinctive feature of this method is the fact that the object of minimization is a numerical model for calculation of the dynamics of realistic beam in the realistic accelerating fields. Such approach allows solving optimization problems in the full setting of the problem. There exist no limitations on the kinds of devices being optimized: magnetic quadrupoles, accelerating gaps etc. It is possible to carry out simultaneous optimization of the matching line parameters and values of magnetic lens quadrupole gradients along the accelerating section. Calculation of the optimum parameters of the marching line for the measured Ar⁺¹⁰ beam distribution is presented with the current of 10 emA; for the calculated parameters output beam parameters are presented. Представлено методику визначення оптимальних параметрів узгоджуючої лінії післяобдиркової ділянки прискорювача UNILAC (структура Альвареця). Особливістю даної методики є те, що об'єктом оптимізації є чисельна модель динаміки реального пучка в реальних прискорювальних полях. Такий підхід дозволяє вирішувати оптимізаційні задачі в повній постановці для будь-яких вхідних розподілів пучка. При цьому немає ніяких обмежень на види пристроїв, що оптимізуються: це можуть бути магнітні квадруполі, прискорюючі зазори й т.д. Є можливість одночасно проводити оптимізацію параметрів узгоджуючої лінії і величин квадрупольних градієнтів магнітних лінз уздовж прискорювальної секції. Наведено розрахунок оптимальних параметрів узгоджуючої лінії для експериментально виміряного вхідного розподілу пучка часток Ar⁺¹⁰ при струмі 10 mA, представлені вихідні параметри пучка для обчислених параметрів. Представлена методика определения оптимальных параметров согласующей линии постобдирочного участка ускорителя UNILAC (структура Альвареца). Особенностью данной методики является то, что объектом оптимизации является численная модель динамики реального пучка в реальных ускоряющих полях. Такой подход позволяет решать оптимизационные задачи в полной постановке для любых входных распределений пучка. При этом нет никаких ограничений на виды оптимизируемых устройств: это могут быть магнитные квадруполи, ускоряющие зазоры и т.д. Имеется возможность одновременно проводить оптимизацию параметров согласующей линии и величин квадрупольных градиентов магнитных линз вдоль ускоряющей секции. Приведен расчет оптимальных параметров согласующей линии для экспериментально измеренного входного распределения пучка частиц Ar⁺¹⁰ при токе 10 mA, представлены выходные параметры пучка для вычисленных параметров.